Wool bezoar in a ten yearold girl. - do Campo, Magela; Peyroulou, Alfredo; Bueno, Eva; Montero, Mario (Cirugía del Uruguay, 1987)
Bezoar is a rare pathology, lhat is generally asso• ciated with psyquiatric diseases as we could observe in our palien!. Diagnosis was easily done based in anamnesis 1:md radiology. A gastrotomy for foreign body extraction was performed. Postoperatory evolution was without inciden Is.